Effect of Mindfulness Meditation on Symptoms of Stress and Depression in Cancer outpatients of Sri Lanka. (MeSADISC study) (Bangladesh Journal of Medical Science, 2025)
Objectives This intervention study aimed to evaluate mindfulness meditation as a method of treatment for cancer outpatients for stress reduction and control of symptoms of depression and to find out effects of socio demographic differences.Method Cancer outpatients were randomly selected on separate clinic dates at the National Cancer Institute of Sri Lanka and were enrolled as cases (n=44) and controls (n=30). Volunteers followed training sessions once weekly in addition to home based mindfulness meditation. All participants were asked to complete the “Beck’s Depression” and “Symptoms of Stress” questionnaires prior to intervention and at each session. Controls were assessed based on the identical questionnaire at start and end of 9 weeks. Both groups were heterogeneous in age, sociodemographic characteristics and cancer types / stage.Result At the end of the intervention, patients in the intervention group had significantly lower scores of depressions and stress. Reduction in Beck’s depression score was from 33.21 to 24.56 (p0.05) in the control group. Reduction in Symptoms of Stress Inventory from 21.21 to 10.76 (p